Modeling the relationship between KLCI and monetary policy after the 1997 Asian financial crisis - Abu Hassan Shaari Md Nor,; Ruzita Abdul Rahim,; Hamizah Mohd,; Zaidi Isa,; Ugur Ergun, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Using Johansen multivariate cointegration test with structural break and Granger-causality based on vector error correction model, the interactions between stock prices (KLCI) and monetary policy variables (M1, M2 and interest rate) are examined in the Malaysian setting using monthly data for the post 1997 Asian financial crisis period from January 2000 to May 2008. Four major conclusions can be drawn from the results. First, evidence of significant cointegration relationships prevails only when structural break is considered in the models. Second, among the monetary variables, only interest rate (money market rate, MM) has a direct short-run relationship with stock prices whereas the relationships between monetary aggregates and stock prices are indirect through MM. Third, all three monetary variables consistently show long-run impacts on stock prices. Fourth, between the two monetary aggregates, M2 consistently prevails as an effective monetary policy tool whereas M1 fails to assume such function. The policy implication of this study is that Bank Negara Malaysia can rely on interest rate rather than money supply as short-term measure to manage the stock market more effectively. However, in the long-run, both interest rate and money supply (specifically M2) can be relied upon to monitor the stock market condition. Investors in the meantime may interpret results of this study as supporting evidence that the stock market in Malaysia is still inefficient. Accordingly, they should exploit new information triggered by changes in monetary policy stance to formulate their future investment strategy